Toxic and signaling effects of the anaesthetic lidocaine on rice cultured cells - Lucia Sylvain Bonfanti; Delphine Arbelet-Bonnin; Frédéric Filaine; Christophe Lalanne; Aurélien Renault; Patrice Meimoun; Patrick Laurenti; Etienne Grésillon; François Bouteau (Plant Signaling & Behavior)
Most studies on anesthesia focus on the nervous system of mammals due to their interest in medicine. The fact that any life form can be anaesthetised is often overlooked although anesthesia targets ion channel activities that exist in all living beings. This study examines the impact of lidocaine on rice (Oryza sativa). It reveals that the cellular responses observed in rice are analogous to those documented in animals, encompassing direct effects, the inhibition of cellular responses, and the long-distance transmission of electrical signals. We show that in rice cells, lidocaine has a cytotoxic effect at a concentration of 1%, since it induces programmed reactive oxygen species (ROS) and caspase-like-dependent cell death, as already demonstrated in animal cells. Additionally, lidocaine causes changes in membrane ion conductance and induces a sharp reduction in electrical long-distance signaling following seedlings leaves burning. Finally, lidocaine was shown to inhibit osmotic stress-induced cell death and the regulation of Ca2+ homeostasis. Thus, lidocaine treatment in rice and tobacco (Nicotiana benthamiana) seedlings induces not only cellular but also systemic effects similar to those induced in mammals.